Assessment of Agrimonia eupatoria L. and Lipophosphonoxin (DR-6180) Combination for Wound Repair: Bridging the Gap Between Phytomedicine and Organic Chemistry - Kaňuchová, Miriam; Brindza Lachová, Veronika; Bogdanová, Kateřina; Sabová, Jana; Bonová, Petra; Vasilenko, Tomáš; Kováč, Ivan; Novotný, Martin; Mitrengová, Petra; Sahatsapan, Nitjawan; Čoma, Matúš; Švajdlenka, Emil; et al. (Biomolecules, 2024)
Agrimonia eupatoria L. (AE) has a rich tradition of use in wound healing improvement across various cultures worldwide. In previous studies, we revealed that Agrimonia eupatoria L. water extract (AE) possesses a rich polyphenolic composition, displaying remarkable antioxidant properties. Our investigations also demonstrated that lipophosphonoxin (LPPO) exhibited antibacterial efficacy in vitro while preserving the proliferation and differentiation of fibroblasts and keratinocytes. Building upon our prior findings, in this study, we intended to examine whether a combination of AE and LPPO could enhance skin wound healing while retaining antibacterial attributes. The antibacterial activity of AE/LPPO against Staphylococcus aureus was evaluated, alongside its effects on fibroblast-to-myofibroblast transition, the formation of extracellular matrix (ECM), and endothelial cells and keratinocyte proliferation/phenotype. We also investigated AE/LPPO's impact on TGF-β1 and VEGF-A signaling in keratinocytes/fibroblasts and endothelial cells, respectively. Additionally, wound healing progression in rats was examined through macroscopic observation and histological analysis. Our results indicate that AE/LPPO promotes myofibroblast-like phenotypic changes and augments ECM deposition. Clinically relevant, the AE/LPPO did not disrupt TGF-β1 and VEGF-A signaling and accelerated wound closure in rats. Notably, while AE and LPPO individually exhibited antibacterial activity, their combination did not lead to synergism, rather decreasing antibacterial activity, warranting further examination. These findings underscore substantial wound healing improvement facilitated by AE/LPPO, requiring further exploration in animal models closer to human physiology.
Keywords: Keratinocytes; skin tissue; Transforming Growth Factor beta1; phytotherapy; potkani Sprague-Dawley; keratinocyty; Humans; zvířata; Plant Extracts; Anti-Bacterial Agents; Fibroblasts; Rats, Sprague-Dawley; regeneration; hojení ran; mužské pohlaví; Male; Animals; Agrimonia; krysa rodu Rattus; Staphylococcus aureus; Wound Healing; rostlinné extrakty; extracellular matrix; vaskulární endoteliální růstový faktor A; Rats; antibakteriální látky; proliferace buněk; repair; lidé; fibroblasty; Cell Proliferation; Vascular Endothelial Growth Factor A; transformující růstový faktor beta1